Ceramic copper-clad substrate, preparation method thereof and semiconductor device
Through electrochemical deposition treatment, pure Cu2O oxide layer is formed and applied to the ceramic substrate at high temperature, which solves the problems of oxide layer uniformity and environmental pollution in the preparation of traditional ceramic copper clad substrates, and improves the reliability and application of ceramic copper clad substrates. quality.
Patent Information
- Application Number
- CN202411794882.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the preparation process of traditional ceramic copper clad substrates, dry oxidation is difficult to regulate the uniformity and thickness of the Cu2O layer. The use of strong oxidants by wet oxidation leads to environmental pollution and health risks, and it is easy to form CuO heterogeneous phases, reducing the quality of bonding.
Electrochemical deposition treatment is performed using copper sulfate pentahydrate and sodium lactate solution to control the current density within the range of 0.4-1mA/cm² to form a pure phase Cu2O oxide layer, combined with high-temperature compressing of ceramic substrates to avoid the formation of CuO impurities, reduce process costs and environment pollute.
It improves the reliability and bonding quality of ceramic copper clad substrates, reduces process costs, avoids environmental pollution and health risks, forms a stable and reliable Cu2O oxide layer, and enhances the reliability of ceramic copper clad substrates.
Smart Images

Figure CN119263869A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor device manufacturing, and in particular relates to a ceramic copper-clad substrate and a preparation method thereof, and a semiconductor device. Background Art
[0002] Ceramic copper-clad substrates have the advantages of high thermal conductivity and low dielectric constant and have been widely used in semiconductor devices. Ceramic copper-clad substrates are usually made of copper foil and ceramic substrates through direct copper bonding (DBC, Direct Bonded Copper). In order to achieve a close bond between the copper foil and the ceramic substrate, and to solve the problem of mismatched thermal expansion coefficients after the copper material and the ceramic substrate are combined, a layer of copper-oxygen spinel structure compound needs to be formed between the copper foil and the ceramic substrate, which leads to the need to introduce oxygen between the copper foil and the ceramic substrate.
[0003] At present, in the traditional process, a Cu2O layer is formed on the surface of the copper foil by dry oxidation or wet oxidation. The Cu2O layer reacts with Al2O3 at high temperature to form a CuAlO2 spinel compound. This spinel compound can fit the copper foil and the ceramic substrate tightly, solving the problem of mismatch in thermal expansion coefficients between the copper foil and the ceramic substrate. Among them, dry oxidation generally heats the surface of the copper foil in a low oxygen partial pressure environment to form a thin layer of Cu2O. However, this method is difficult to control the uniformity and thickness of the Cu2O layer, and requires Strict control of oxygen partial pressure results in high process costs; wet oxidation generally involves strong oxidants such as KMnO4, Na2S2O8, K2S2O8, which are not in line with the development principles of green environmental protection, are very likely to pollute the production environment, and are not conducive to the health of operators; in addition, whether dry oxidation or wet oxidation is used, it is easy to form a CuO impurity phase in the Cu2O layer, resulting in the generation of CuAl2O4 spinel structure compounds when the copper foil is bonded to the ceramic substrate, thereby reducing the bonding quality and causing poor reliability of the ceramic copper-clad substrate.
[0004] In view of the above, the present invention is proposed. Summary of the invention
[0005] The present application provides a ceramic copper-clad substrate and a preparation method thereof and a semiconductor device, aiming to solve the above-mentioned problems or at least alleviate the defects existing in the above-mentioned prior art.
[0006] The first aspect of the present application provides a method for preparing a ceramic copper-clad substrate, comprising: Dissolving copper sulfate pentahydrate in a sodium lactate solution to obtain a mixed solution, adding liquid alkali to the mixed solution to adjust the pH value to a preset value, and obtaining a sedimentation solution; The copper foil is surface treated, the surface treated copper foil is placed in a deposition solution, and a direct current electrochemical deposition treatment is performed on the surface treated copper foil at a current density of 0.4-1 mA / cm² to obtain a wet oxidized copper foil having a pure phase Cu2O oxide layer formed on the surface; The wet-oxidized copper foil is bonded to the ceramic substrate and then subjected to high-temperature lamination to obtain a ceramic copper-clad substrate.
[0007] The present application optimizes the design of the preparation method of the ceramic copper-clad substrate, adopts a solution made of copper sulfate pentahydrate, sodium lactate solution and liquid alkali as a deposition liquid during electrochemical deposition treatment, copper sulfate pentahydrate as the main salt can provide copper ions for the formation of a pure phase Cu2O oxide layer, sodium lactate as a complexing agent can play a complexing role to prevent copper ion precipitation during the pH increase of the deposition liquid system, and liquid alkali can provide hydroxide ions for the reduction reaction occurring at the cathode during the electrochemical deposition treatment, so as to facilitate the formation of a pure phase Cu2O oxide layer on the surface of the copper foil after wet oxidation; it should be emphasized that the present application is 0.4-1mA / The copper foil is subjected to direct current electrochemical deposition at a current density of 10000 cm². When the current density of the electrochemical deposition treatment is greater than 1mA / cm², the deposition product will be converted into CuO, resulting in the appearance of impurities in the Cu2O oxide layer, while the current density less than 0.4mA / cm² will result in poor uniformity of the formed Cu2O oxide layer and a low deposition rate. By controlling the current density within the range of 0.4-1mA / cm², the purity and morphology of the Cu2O oxide layer can be comprehensively controlled, thereby effectively improving the bonding quality of the copper foil and the ceramic substrate after wet oxidation, thereby significantly improving the reliability of the ceramic copper-clad substrate.
[0008] Therefore, the present application adopts a wet method combined with electrochemical deposition. The reagents used in the deposition liquid are low-priced, the process operation is simple, and there is no need to control the oxygen partial pressure and other complex processes, so the process cost is significantly reduced. At the same time, copper sulfate pentahydrate, sodium lactate and liquid alkali are not highly oxidizing and corrosive, and the formula is more environmentally friendly, in line with the development principle of green environmental protection, avoiding pollution to the production environment, and effectively protecting the health of operators. Compared with traditional dry oxidation methods or wet oxidation methods, the oxidation product formed between the copper foil and the ceramic substrate of the present application is a pure phase Cu2O oxide layer, and no CuO impurities are generated. The film formation is stable and reliable, so as to avoid the formation of CuAl2O4 spinel structure when the copper foil and the ceramic substrate are bonded and bonded, thereby reducing the bonding quality.
[0009] In some embodiments, the above preparation method satisfies at least one of the following conditions: (1) The concentration of copper sulfate pentahydrate in the sedimentation liquid is 40-120 g / L; the concentration of sodium lactate in the sedimentation liquid is 300-400 g / L; the pH of the sedimentation liquid is 9-12; (2) The liquid alkali is sodium hydroxide; (3) The copper foil is oxygen-free copper with a thickness of 0.2-0.4 mm; (4) The ceramic substrate is any one of an Al2O3 ceramic substrate, an AlN ceramic substrate, and a ZTA ceramic substrate, and the thickness of the ceramic substrate is 0.3 mm to 0.4 mm; (5) dissolving copper sulfate pentahydrate in sodium lactate solution under magnetic stirring at a stirring speed of 550-650 r / min and a temperature of 50-70°C; (6) High-temperature bonding is carried out in a nitrogen atmosphere, the bonding temperature is 1065-1083°C, and the bonding time is 10-20 minutes.
[0010] In some embodiments, the anode in the electrochemical deposition process is 304 stainless steel, the cathode is a surface-treated copper foil, and the distance between the electrodes is controlled to be 15 mm, and the current is provided by a constant current source.
[0011] In some embodiments, the electrochemical deposition process is performed at a deposition temperature of 50-70° C. and a deposition time of 20-30 minutes; and the electrochemical deposition process is performed under magnetic stirring.
[0012] In some embodiments, the particles on the surface of the pure phase Cu2O oxide layer are closely arranged in sheets and evenly distributed; the thickness of the pure phase Cu2O oxide layer is 5 μm-10 μm.
[0013] In some embodiments, the surface treatment of the copper foil satisfies at least one of the following conditions: A. Remove oil stains and oxide film on the surface of copper foil; B. Apply insulating tape to the non-bonded surface of the copper foil.
[0014] In some embodiments, removing oil stains and oxide film on the surface of copper foil specifically includes: immersing the copper foil in a degreasing solution for ultrasonic cleaning to obtain degreased copper foil, washing the degreased copper foil with deionized water and then immersing it in a hydrochloric acid solution for ultrasonic cleaning to obtain a surface-treated copper foil.
[0015] In some embodiments, before bonding the wet-oxidized copper foil to the ceramic substrate and performing high-temperature bonding, the insulating tape on the wet-oxidized copper foil is removed and ionized water is rinsed, and then the wet-oxidized copper foil after ionized water is placed in ethanol for ultrasonic cleaning.
[0016] A second aspect of the present application provides a ceramic copper-clad substrate, which is prepared using the above-mentioned preparation method.
[0017] A third aspect of the present application provides a semiconductor device, comprising the above-mentioned ceramic copper-clad substrate or an electronic component made of the ceramic copper-clad substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The XRD spectrum (left side) and Raman analysis spectrum (right side) of the copper foil after wet oxidation in Example 1 of the present application are shown; Figure 2 is a SEM image of the surface (left side) and cross section (right side) of the copper foil after wet oxidation in Example 2 of the present application; Figure 3 These are SEM images of the surface (left side) and cross section (right side) of the copper foil after wet oxidation in Example 3 of the present application. DETAILED DESCRIPTION
[0020] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0021] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0022] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0023] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0024] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0025] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0026] Based on the foregoing, the general inventive concept of the present application is to optimize the design of the preparation method of the ceramic copper-clad substrate, form a cuprous oxide layer on the surface of the copper foil by electrochemical deposition treatment, and optimize the design of the deposition liquid components during the electrochemical deposition treatment, and use low-cost and environmentally friendly reagents as component raw materials of the deposition liquid to reduce process costs and avoid environmental pollution. At the same time, by controlling the current density during the electrochemical deposition treatment, a pure-phase cuprous oxide layer with high uniformity is obtained to avoid the formation of mixed-phase copper oxide after the electrochemical deposition treatment, thereby improving the reliability of the copper foil and the ceramic substrate during bonding.
[0027] Based on the above general inventive concept, an embodiment of the present application provides a method for preparing a ceramic copper-clad substrate, comprising: S100, dissolving copper sulfate pentahydrate in a sodium lactate solution to obtain a mixed solution, adding liquid alkali to the mixed solution to adjust the pH value to a preset value, and obtaining a sedimentation solution; S200, performing surface treatment on the copper foil, placing the surface treated copper foil in a deposition solution, and performing direct current electrochemical deposition treatment on the copper foil at a current density of 0.4-1 mA / cm² to obtain a wet oxidized copper foil having a pure phase Cu2O oxide layer formed on the surface; S300, bonding the wet-oxidized copper foil to the ceramic substrate and performing high-temperature bonding to obtain a ceramic copper-clad substrate.
[0028] In step S100 of this embodiment, copper sulfate pentahydrate is used as the main salt of the deposition solution to provide copper ions for the formation of a pure phase Cu2O oxide layer. Sodium lactate is used as a chelating agent to play a chelating role to prevent copper ion precipitation after liquid alkali is added to the mixed solution. Liquid alkali can provide hydroxide ions required by the cathode during the electrochemical deposition process. Therefore, the deposition solution contains copper ions, lactate ions and hydroxide ions, which provides a necessary environment for subsequent electrochemical deposition reactions. At the same time, the component raw materials of the deposition solution are inexpensive and do not have strong oxidizing properties, thereby avoiding pollution to the production environment and benefiting the health of operators.
[0029] Furthermore, in step S200, before the electrochemical deposition treatment, the copper foil needs to be surface treated to remove impurities such as oil stains and oxides on its surface and improve the bonding ability between the copper foil and the deposition liquid; the surface treatment method may include mechanical polishing, chemical cleaning, and applying insulating tape to the side that does not need to be bonded; the surface-treated copper foil is placed in the deposition liquid and ensured to be completely immersed; then, the copper foil is subjected to direct current electrochemical deposition treatment within a current density range of 0.4-1 mA / cm² to ensure that a pure phase Cu2O oxide layer is formed on the surface of the copper foil; during the electrochemical deposition treatment, the copper ions in the deposition liquid obtain electrons on the surface of the copper foil and are reduced to Cu2O, and a uniform oxide layer is formed on the surface of the copper foil to obtain a wet-oxidized copper foil.
[0030] During the electrochemical deposition process, within the current density range of 0.4-1 mA / cm², when the current density increases, the deposited Cu2O morphology becomes denser; however, if the current density is too high (exceeding 1 mA / cm²), impurities such as CuO may be generated, and if the current density is too low (below 0.4 mA / cm²), the deposition rate is too slow, which is not conducive to the formation of a dense Cu2O oxide layer.
[0031] Through step S300, the wet-oxidized copper foil and the ceramic substrate are bonded together and subjected to high-temperature lamination. The Cu2O oxide layer reacts with the oxide (such as Al2O3) on the surface of the ceramic substrate to generate a CuAlO2 spinel structure compound. The spinel structure compound has a strong binding force and can firmly combine the wet-oxidized copper foil and the ceramic substrate to obtain a ceramic copper-clad substrate. At the same time, since the thermal expansion coefficients of Cu2O and the ceramic substrate are similar, the generated spinel structure compound can also effectively solve the problem of thermal expansion coefficient mismatch between the copper foil and the ceramic substrate.
[0032] It should be noted that the current density of the direct current electrochemical deposition treatment on the copper foil in the embodiment of the present application is 0.4-1 mA / cm². For example, the current density of the direct current electrochemical deposition treatment on the copper foil can be 0.4 mA / cm², 0.45mA / cm², 0.50 mA / cm², 0.55 mA / cm², 0.60 mA / cm², 0.65 mA / cm², 0.70 mA / cm², 0.75 mA / cm², 0.80 mA / cm², 0.85 mA / cm², 0.90 mA / cm², 0.95 mA / cm², 1mA / cm² or any current density within the range of 0.4-1 mA / cm².
[0033] In some embodiments, the concentration of copper sulfate pentahydrate in the deposition liquid is 40-120 g / L. Too low a concentration of copper sulfate pentahydrate will result in a slow deposition rate, affecting production efficiency; too high a concentration will increase the viscosity of the deposition liquid, affecting the mass transfer process, and increasing the probability of side reactions; the concentration of copper sulfate pentahydrate in the deposition liquid is 40-120 g / L, which not only ensures sufficient copper ion supply, but also avoids the adverse effects of excessive concentration. The concentration of sodium lactate in the deposition liquid is 300-400 g / L. Within this range, the complexing effect can be ensured while avoiding excessive sodium lactate from having a negative impact on the deposition process.
[0034] The pH of the deposition solution in the embodiment of the present application is 9-12, which is conducive to ensuring the formation of a pure phase Cu2O oxide layer on the surface of the copper foil; because copper ions are more easily reduced to Cu2O under alkaline conditions, and too low a pH value (acidic or neutral conditions) is not conducive to the formation of Cu2O, and easily leads to the easy generation of CuO; at the same time, too high a pH value may make the solution too alkaline, increasing the risk of side reactions.
[0035] In some embodiments, the liquid alkali is sodium hydroxide, which can provide hydroxide ions and is inexpensive, thereby helping to reduce manufacturing costs.
[0036] In some embodiments, the copper foil is oxygen-free copper and has a thickness of 0.2-0.4 mm.
[0037] It should be noted that the oxygen-free copper in the embodiment of the present application is also called high-purity copper or pure copper, which is usually higher in purity than ordinary electrolytic copper and contains very little oxygen and other impurity elements, so as to reduce the cleaning cost of the copper foil and ensure that a pure phase Cu2O oxide layer is formed after electrochemical deposition. The thickness of the copper foil is 0.2-0.4 mm, preferably 0.3 mm, so as to provide structural support for the load of the pure phase Cu2O oxide layer.
[0038] In some embodiments, the ceramic substrate is any one of an Al2O3 ceramic substrate, an AlN ceramic substrate, and a ZTA ceramic substrate, wherein an aluminum oxide (Al2O3) ceramic substrate is one of the most commonly used substrate materials in the electronics industry, having high strength, high chemical stability, high thermal conductivity, and abundant raw material sources, and its thermal expansion coefficient is close to that of silicon; an aluminum nitride (AlN) ceramic substrate has high thermal conductivity and an expansion coefficient matching that of silicon, and is an ideal heat dissipation and packaging material; a zirconium oxide toughened alumina (ZTA) ceramic substrate improves the reliability, corrosion resistance, and chemical stability of the substrate by doping zirconium-doped alumina ceramics; the above-mentioned ceramic substrates are all beneficial to improving the reliability of ceramic copper-clad substrates.
[0039] In some embodiments, the thickness of the ceramic substrate is 0.3 mm-0.4 mm. The thickness of the ceramic substrate of 0.3 mm to 0.4 mm can take into account the strength, thermal conductivity, processing performance and cost of the substrate.
[0040] In some embodiments, the dissolution of copper sulfate pentahydrate in the sodium lactate solution is carried out under magnetic stirring, which is beneficial to promote the dissolution of copper sulfate pentahydrate. The stirring speed is 550-650r / min and the temperature is 50-70°C, so that copper sulfate pentahydrate is quickly dissolved in the sodium lactate solution.
[0041] In some embodiments, high-temperature bonding is performed in a nitrogen atmosphere at a bonding temperature of 1065-1083° C. for a bonding time of 10-20 min to ensure that the Cu2O layer reacts with Al2O3 at high temperature to generate a CuAlO2 spinel structure compound, thereby improving the reliability of the ceramic copper-clad substrate.
[0042] In some embodiments, the anode in the electrochemical deposition process is 304 stainless steel. 304 stainless steel is often used as an anode material for electrochemical deposition due to its excellent corrosion resistance, good processability and weldability. The cathode in the electrochemical deposition process is a surface-treated copper foil. The copper foil serves as a cathode and is the place where the deposited layer is formed during the electrochemical deposition process. The spacing between the electrodes in the electrochemical deposition process is controlled to be 15 mm. A smaller electrode spacing can shorten the distance of ion migration and increase the deposition rate. The current for the electrochemical deposition process is provided by a constant current source. The constant current source provides a stable current for the electrochemical deposition process, which can effectively control the magnitude and stability of the current, thereby avoiding the influence of current fluctuations on the quality of the deposited layer and ensuring that the deposition process can be carried out according to predetermined conditions.
[0043] The constant current source in the embodiment of the present application is also called a current source or a steady current source. The working principle of the constant current source is based on feedback control technology. It monitors the output current and compares it with the set reference current, and then automatically adjusts the output voltage or the working state of the current control element to keep the output current constant. The constant current source is a power supply that can output a constant current. No matter how the load changes, it can maintain the stability and accuracy of the output current.
[0044] In some embodiments, the electrochemical deposition process is carried out at a deposition temperature of 50-70° C. and a deposition time of 20-30 minutes; the electrochemical deposition process is carried out under magnetic stirring to promote uniform distribution and diffusion of metal ions in the deposition liquid and eliminate concentration polarization on the surface of the deposition liquid, thereby improving the deposition rate and uniformity, and magnetic stirring can effectively improve the fluidity and mass transfer performance of the electrolyte, so that more metal ions can reach the cathode surface and participate in the deposition process, which helps to improve the uniformity and density of the deposited layer, and reduce the generation of defects and impurities, so as to facilitate the formation of a uniform and dense pure phase Cu2O oxide layer.
[0045] It should be noted that, in this embodiment, the deposition temperature is one of the important factors affecting the electrochemical deposition process. When the deposition temperature is in the range of 50-70°C, the metal ions in the electrolyte (i.e., the deposition solution) have high activity, which is conducive to their reduction and deposition on the cathode surface; at the same time, the appropriate temperature can also increase the conductivity of the electrolyte, promote the migration and diffusion of ions, and thus accelerate the deposition rate.
[0046] During the electrochemical deposition process, a deposition time of 20-30 minutes can make the formed pure phase Cu2O oxide layer have an appropriate thickness. When the deposition time is within the range of 20-30 minutes, extending the deposition time can increase the thickness of the deposited Cu2O oxide layer. However, when the deposition time exceeds 30 minutes, the Cu2O oxide layer will fall off the surface of the copper foil due to the long deposition time, and the thickness of the formed Cu2O oxide layer is too large, which seriously affects the subsequent bonding quality.
[0047] In some embodiments, the particles on the surface of the pure phase Cu2O oxide layer are closely arranged and evenly distributed in a flake shape, so as to improve the tightness of the bonding between the copper foil and the ceramic substrate.
[0048] In some embodiments, the thickness of the pure phase Cu2O oxide layer is 5μm-10μm. The thickness of the pure phase Cu2O oxide layer is appropriate to facilitate reaction with Al2O3 to generate CuAlO2 spinel structure compound, promote close bonding between the copper foil and the ceramic substrate, and facilitate improving the reliability of the ceramic copper clad substrate.
[0049] In some embodiments, surface treatment of the copper foil includes: removing oil stains and oxide films on the surface of the copper foil.
[0050] In some embodiments, in order to achieve single-sided oxidation of the copper foil, the surface treatment of the copper foil also includes applying insulating tape to the non-bonding surface of the copper foil, which can conveniently control the area where the cuprous oxide oxide layer appears on the copper foil to achieve single-sided oxidation of the copper foil. During the bonding process of the unoxidized surface, no orange peel defects will be formed due to high-temperature decomposition or reaction of Cu2O, which significantly improves the solderability of the ceramic copper-clad substrate when the chip is subsequently soldered.
[0051] Furthermore, removing the oil stains and oxide film on the surface of the copper foil specifically includes: immersing the copper foil in a degreasing solution (such as degreasing solution JX-1020N) for ultrasonic cleaning to obtain a degreased copper foil, washing the degreased copper foil with deionized water and then immersing it in a hydrochloric acid solution for ultrasonic cleaning to obtain a surface-treated copper foil, so as to avoid the introduction of impurities into the subsequently formed Cu2O oxide layer.
[0052] In some embodiments, before bonding the wet-oxidized copper foil to the ceramic substrate and performing high-temperature bonding, the insulating tape on the wet-oxidized copper foil is removed and ionized water is rinsed, and then the wet-oxidized copper foil after ionized water is placed in ethanol for ultrasonic cleaning and drying to prevent impurities in the deposition liquid from remaining on the surface of the wet-oxidized copper foil.
[0053] Another embodiment of the present application provides a ceramic copper-clad substrate, which is prepared by the preparation method of the above embodiment.
[0054] Another embodiment of the present application provides a semiconductor device, including the above-mentioned ceramic copper-clad substrate or an electronic component made of the ceramic copper-clad substrate.
[0055] The following examples describe the disclosure of the present application in more detail, and these examples are merely illustrative, as it will be apparent to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all reagents and raw materials used in the examples are commercially available or synthesized according to conventional methods, and the instruments used in the examples are commercially available.
[0056] Example 1 Dissolve copper sulfate pentahydrate in a sodium lactate solution, then add deionized water and stir until no precipitation is obtained to obtain a mixed solution, add an appropriate amount of sodium hydroxide to the mixed solution to adjust the pH to 11, and obtain a sedimentation solution; the concentration of copper sulfate pentahydrate in the sedimentation solution is 100 g / L, and the concentration of sodium lactate is 330 g / L; The copper foil was immersed in a 10% JX-1020N degreasing solution for 10 minutes of ultrasonic cleaning. After the ultrasonic cleaning, it was washed with deionized water. After that, the copper foil washed with deionized water was immersed in a 3% hydrochloric acid solution for 5 minutes of ultrasonic cleaning. Then, the copper foil was rinsed and dried with alcohol, and a PET insulating tape for electroplating was attached to the non-attached surface of the copper foil. The copper foil with the insulating tape was added to the deposition liquid for direct current electrochemical deposition to obtain a copper foil with a pure phase Cu2O oxide layer formed on the surface after wet oxidation. The anode of the electrochemical deposition treatment was stainless steel, and the cathode was the copper foil with the insulating tape attached. The distance between the electrodes was 15 mm. The current density during the electrochemical deposition treatment was 0.6 mA / cm², the deposition temperature was 60°C, and the deposition time was 30 minutes. The insulating tape on the unoxidized surface of the wet-oxidized copper foil was removed and rinsed with deionized water. After cleaning, the wet-oxidized copper foil was placed in a 96% ethanol solution for ultrasonic cleaning for 5 minutes and dried. The dried wet-oxidized copper foil was bonded to an Al2O3 ceramic substrate under a nitrogen atmosphere for high-temperature lamination to obtain a ceramic copper-clad substrate. The lamination temperature was 1075°C and the lamination time was 15 minutes.
[0057] Example 2 Dissolve copper sulfate pentahydrate in a sodium lactate solution, then add deionized water and stir until no precipitation is obtained to obtain a mixed solution, add an appropriate amount of sodium hydroxide to the mixed solution to adjust the pH to 9, and obtain a sedimentation solution; the concentration of copper sulfate pentahydrate in the sedimentation solution is 50 g / L, and the concentration of sodium lactate is 330 g / L; The copper foil was immersed in a 10% JX-1020N degreasing solution for 10 minutes of ultrasonic cleaning. After the ultrasonic cleaning was completed, it was washed with deionized water. After that, the copper foil washed with deionized water was immersed in a 3% hydrochloric acid solution for 5 minutes of ultrasonic cleaning. Then, the copper foil was rinsed and dried with alcohol, and a PET insulating tape for electroplating was attached to the non-applied surface of the copper foil. The copper foil with the insulating tape was added to the deposition liquid for direct current electrochemical deposition to obtain a copper foil with a pure phase Cu2O oxide layer formed on the surface after wet oxidation. The anode of the electrochemical deposition treatment was stainless steel, and the cathode was the copper foil with the insulating tape attached. The distance between the electrodes was 15 mm. The current density during the electrochemical deposition process was 0.4 mA / cm², the deposition temperature was 60°C, and the deposition time was 20 minutes. The insulating tape on the unoxidized surface of the wet-oxidized copper foil was removed and rinsed with deionized water. After cleaning, the wet-oxidized copper foil was placed in a 96% ethanol solution for ultrasonic cleaning for 5 minutes and dried. The dried wet-oxidized copper foil was bonded to an Al2O3 ceramic substrate under a nitrogen atmosphere for high-temperature lamination to obtain a ceramic copper-clad substrate. The lamination temperature was 1075°C and the lamination time was 15 minutes.
[0058] Example 3 Dissolve copper sulfate pentahydrate in a sodium lactate solution, then add deionized water and stir until no precipitation is obtained to obtain a mixed solution, add an appropriate amount of sodium hydroxide to the mixed solution to adjust the pH to 9, and obtain a sedimentation solution; the concentration of copper sulfate pentahydrate in the sedimentation solution is 50 g / L, and the concentration of sodium lactate is 330 g / L; The copper foil was immersed in a 10% JX-1020N degreasing solution for 10 minutes of ultrasonic cleaning. After the ultrasonic cleaning, it was washed with deionized water. After that, the copper foil washed with deionized water was immersed in a 3% hydrochloric acid solution for 5 minutes of ultrasonic cleaning. Then, the copper foil was rinsed and dried with alcohol, and a PET insulating tape for electroplating was attached to the non-applied surface of the copper foil. The copper foil with the insulating tape was added to the deposition liquid for direct current electrochemical deposition to obtain a copper foil with a pure phase Cu2O oxide layer formed on the surface after wet oxidation. The anode of the electrochemical deposition treatment was stainless steel, and the cathode was the copper foil with the insulating tape attached. The distance between the electrodes was 15 mm. The current density during the electrochemical deposition treatment was 0.6 mA / cm², the deposition temperature was 60°C, and the deposition time was 20 minutes. The insulating tape on the unoxidized surface of the wet-oxidized copper foil was removed and rinsed with deionized water. After cleaning, the wet-oxidized copper foil was placed in a 96% ethanol solution for ultrasonic cleaning for 5 minutes and dried. The dried wet-oxidized copper foil was bonded to an Al2O3 ceramic substrate under a nitrogen atmosphere for high-temperature lamination to obtain a ceramic copper-clad substrate. The lamination temperature was 1075°C and the lamination time was 15 minutes.
[0059] Comparative Example 1 Dissolve copper sulfate pentahydrate in a sodium lactate solution, then add deionized water and stir until no precipitation is obtained to obtain a mixed solution, add an appropriate amount of sodium hydroxide to the mixed solution to adjust the pH to 11, and obtain a sedimentation solution; the concentration of copper sulfate pentahydrate in the sedimentation solution is 100 g / L, and the concentration of sodium lactate is 330 g / L; The copper foil was immersed in a 10% JX-1020N degreasing solution for 10 minutes of ultrasonic cleaning. After the ultrasonic cleaning was completed, it was washed with deionized water. The copper foil washed with deionized water was immersed in a 3% hydrochloric acid solution for 5 minutes of ultrasonic cleaning. Then, the copper foil was rinsed with alcohol and dried. The dried copper foil was added to the deposition solution for direct current electrochemical deposition to obtain a wet oxidized copper foil with an oxide layer containing copper oxide and cuprous oxide on the surface. The anode of the electrochemical deposition treatment was stainless steel, the cathode was copper foil, the distance between the electrodes was 15 mm, the current density during the electrochemical deposition treatment was 1.2 mA / cm², the deposition temperature was 60°C, and the deposition time was 30 minutes. The wet-oxidized copper foil was rinsed with deionized water, and after cleaning, the wet-oxidized copper foil was placed in a 96% ethanol solution for ultrasonic cleaning for 5 minutes and dried; the dried wet-oxidized copper foil was bonded to an Al2O3 ceramic substrate under a nitrogen atmosphere for high-temperature lamination to obtain a ceramic copper-clad substrate, the lamination temperature was 1075°C, and the lamination time was 15 minutes.
[0060] In order to analyze the phase composition of the oxide layer on the wet-oxidized copper foil, the wet-oxidized copper foil prepared in Example 1 was characterized to obtain Figure 1 middle, Figure 1 The left figure (a) in the figure is the XRD spectrum of the copper foil after wet oxidation. Figure 1 The figure on the right (b) is the Raman analysis spectrum of the copper foil after wet oxidation.
[0061] In order to analyze the morphology of the copper foil after wet oxidation, the surface and cross section of the copper foil after wet oxidation prepared in Example 2 and Example 3 were characterized by SEM. The obtained SEM images are as follows: Figure 2 and Figure 3 As shown, Figure 2 : is a SEM image of the surface (left side) and cross section (right side) of the copper foil after wet oxidation in Example 2 of the present application, Figure 3 These are SEM images of the surface (left side) and cross section (right side) of the copper foil after wet oxidation in Example 3 of the present application.
[0062] Combination Figure 1 As can be seen from (a) and (b) in the figure, the wet-oxidized copper foil obtained in Example 1 does not contain copper oxide, and the oxide layer is pure cuprous oxide with high film quality. Figure 2 and Figure 3 It can be seen that the pure phase Cu2O oxide layer on the surface of the copper foil after wet oxidation prepared in Examples 2 and 3 of the present application is tightly arranged in flakes and evenly distributed, and the surface of the oxide layer is smooth and bright and the inside is dense.
[0063] By observing the surfaces of the ceramic substrates prepared in Comparative Example 1 and Example 1, the unbonded surface of the ceramic copper-clad substrate prepared in Comparative Example 1 has a large number of fish-scale wrinkled skin defects and a rough surface, while the unbonded surface of the ceramic copper-clad substrate prepared in Example 1 is smooth without fish-scale wrinkled skin defects.
[0064] Compared with Example 1, in Comparative Example 1, the current density during the electrochemical deposition treatment of Comparative Example 1 is 1.2 mA / cm². The current density is too large, and the oxide layer formed after the electrochemical deposition treatment contains impure copper oxide, which results in the generation of CuAl2O4 spinel structure compounds when the copper foil and the ceramic substrate are bonded and bonded, thereby reducing the bonding quality, resulting in poor reliability of the ceramic copper-clad substrate. In addition, in Comparative Example 1, PET insulating tape is not affixed to the non-bonded surface, and both sides of the copper foil are wet-oxidized. After high-temperature bonding, the Cu2O on the non-bonded surface is decomposed or reacted at high temperature to form fish-scale wrinkled skin defects, resulting in the surface roughness and weldability of the ceramic copper-clad substrate of Comparative Example 1 being inferior to those of Example 1.
[0065] In summary, the reagents used in the deposition liquid of the present invention are inexpensive. Compared with dry oxidation, the process operation is simple, and there is no need to carry out complex processes such as controlling the oxygen partial pressure, so that the cost of DBC copper oxidation is reduced. Neither the main salt nor the complexing agent has strong oxidizing and corrosive properties. The use of the formula of the present invention is more environmentally friendly and reduces the harm to the environment and human health. Moreover, the oxidation product formed on the surface of the copper foil is a single Cu2O phase, and no CuO impurities are generated. The film formation is stable and reliable, and the generation of CuAl2O4 spinel structure compounds during bonding can be avoided, thereby reducing the bonding quality. At the same time, the film thickness and morphology of the copper oxide can be comprehensively controlled by parameters such as current density and deposition time to prepare a uniform, dense, and thickness-controlled pure-phase Cu2O oxide layer, so as to effectively improve the bonding quality and promote the improvement of the reliability of the ceramic copper-clad substrate. In addition, the present application attaches PET insulating tape for electroplating to the non-bonded surface of the copper foil in order to control the area where copper oxide appears, thereby achieving single-sided oxidation of copper and avoiding the formation of orange peel defects due to high-temperature decomposition or reaction of Cu2O during the bonding process of the non-oxidized surface, thereby improving the solderability of the DBC ceramic copper-clad substrate.
[0066] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a ceramic copper-clad substrate, characterized in that: include: Dissolving copper sulfate pentahydrate in a sodium lactate solution to obtain a mixed solution, adding liquid alkali to the mixed solution to adjust the pH value to a preset value, and obtaining a sedimentation solution; Surface treatment is performed on the copper foil, the surface-treated copper foil is placed in the deposition solution, and the surface-treated copper foil is subjected to direct current electrochemical deposition treatment at a current density of 0.4-1 mA / cm² to obtain a wet-oxidized copper foil having a pure phase Cu2O oxide layer formed on the surface; The wet-oxidized copper foil is bonded to a ceramic substrate and subjected to high-temperature lamination to obtain a ceramic copper-clad substrate.
2. The preparation method according to claim 1, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The concentration of copper sulfate pentahydrate in the sedimentation liquid is 40-120 g / L; the concentration of sodium lactate in the sedimentation liquid is 300-400 g / L; the pH of the sedimentation liquid is 9-12; (2) The liquid alkali is sodium hydroxide; (3) The copper foil is oxygen-free copper with a thickness of 0.2-0.4 mm; (4) The ceramic substrate is any one of an Al2O3 ceramic substrate, an AlN ceramic substrate, and a ZTA ceramic substrate, and the thickness of the ceramic substrate is 0.3 mm to 0.4 mm; (5) The step of dissolving copper sulfate pentahydrate in sodium lactate solution is carried out under magnetic stirring at a stirring speed of 550-650 r / min and a temperature of 50-70° C.; (6) The high-temperature bonding is carried out in a nitrogen atmosphere, the bonding temperature is 1065-1083°C, and the bonding time is 10-20 minutes.
3. The preparation method according to claim 2, characterized in that: The anode in the electrochemical deposition process is 304 stainless steel, the cathode is the copper foil after the surface treatment, and the distance between the electrodes is controlled to be 15 mm, and the current is provided by a constant current source.
4. The preparation method according to claim 2, characterized in that: The electrochemical deposition process is carried out at a deposition temperature of 50-70° C. and a deposition time of 20-30 minutes; the electrochemical deposition process is carried out under magnetic stirring.
5. The preparation method according to claim 1, characterized in that: The particles on the surface of the pure phase Cu2O oxide layer are closely arranged in sheets and evenly distributed; The thickness of the pure phase Cu2O oxide layer is 5 μm-10 μm.
6. The preparation method according to claim 2, characterized in that: The surface treatment of the copper foil satisfies at least one of the following conditions: A. Remove oil stains and oxide film on the surface of copper foil; B. Apply insulating tape to the non-bonded surface of the copper foil.
7. The preparation method according to claim 6, characterized in that: The method of removing the oil stains and oxide film on the surface of the copper foil specifically includes: immersing the copper foil in a degreasing solution for ultrasonic cleaning to obtain a degreasing copper foil, washing the degreasing copper foil with deionized water and then immersing it in a hydrochloric acid solution for ultrasonic cleaning to obtain a surface-treated copper foil.
8. The preparation method according to claim 6, characterized in that: Before bonding the wet-oxidized copper foil to the ceramic substrate and performing high-temperature bonding, the method also includes removing the insulating tape on the wet-oxidized copper foil and rinsing it with ionized water, and then placing the wet-oxidized copper foil rinsed with ionized water in ethanol for ultrasonic cleaning.
9. A ceramic copper-clad substrate, characterized in that: The method is prepared by any one of claims 1 to 8.
10. A semiconductor device, characterized in that: It comprises the ceramic copper clad substrate as claimed in claim 9 or an electronic component made of the ceramic copper clad substrate.
Citation Information
Patent Citations
Ceramic copper-clad substrate and preparation method thereof
CN102206098A
Preparation method of aluminum nitride ceramic copper clad substrate
CN109608221A
Cuprous oxide film with high photoelectrochemical performance and preparation method thereof
CN112853423A
Aluminum nitride copper-coated ceramic as well as preparation method and application thereof
CN115286415A
Ceramic copper-clad plate and preparation method thereof
CN116180167A